Efficacy of microscale/nanoscale aqueous ozone on the removal of Bacillus spp. biofilms from polyethersulfone membranes in the dairy industry - Henderson, Rachael Michelle (Kansas State University, 2020)
Biofilm formation on polyethersulfone (PES) membranes in the dairy industry is a concern to food safety and public health. Fouling of PES membranes leads to biofilm formation on membrane surfaces, resulting in reduction in membrane performance and premature replacement of membranes. The dairy industry must develop technology to discourage biofilm attachment, while also finding a more efficient, eco-friendly approach to biofilm removal from dairy processing equipment. Fouling of PES membrane surfaces creates an environment in which bacterial attachment and biofilm formation thrive. Biofilm removal from dairy processing membranes has become a point of interest as cost of producing quality products continues to rise. Experimentation was carried out in two phases. Phase 1 evaluated the half-life of microscale/nanoscale aqueous ozone (MNAO) using a factorial design, with pH (2, 4, and 7) and temperature (5, 10, and 20°C) as independent factors with two replications. After statistical analysis of the half-life study using a completely randomized design, a pH of 4 at 10°C for MNAO was used in further studies. This study then evaluated the efficiency of MNAO on removal of biofilms from PES membranes. Phase 2A first compared the efficacy of a deionized water wash and MNAO on Bacillus cereus and Bacillus licheniformis biofilms grown on PES membranes. MNAO was more effective (p≤0.05) than the water wash with an average reduction of 1.9 log₁₀ cfu/cm² for Bacillus cereus, and 1.2 log₁₀ cfu/cm² for Bacillus. licheniformis, respectively. The MNAO membrane wash reduced B. licheniformis counts on membranes by 2.3 log cycles, while the water wash reduced the population level by 1.9 log cycles (p≤0.05). Both the Bacillus cereus and Bacillus licheniformis data were compared to a non-treated control membrane. Phase 2B analyzed the efficacy of a typical clean-in-place (CIP) cycle used in the dairy industry compared to a CIP cycle followed by MNAO wash. Treatment of B. cereus biofilms using a standard CIP protocol or the CIP+MNAO resulted in significant (p≤0.05) population reductions of 3.8 and 4.1 log₁₀ cfu/cm² respectively. A significant difference was observed when comparing Side A and Side B data (p≤0.05). For Bacillus licheniformis containing biofilms, both treatments provided significant population reductions (p≤0.05) compared to the untreated control. Phase 2C studied the efficacy of a typical CIP system alone in comparison to an MNAO wash followed by a typical CIP system. In the Bacillus cereus and Bacillus licheniformis study, CIP and MNAO+CIP treatments significantly reduced (p≤0.05) population levels of both organisms by 3.4 to 4.7 log cycles respectively; however, the reductions observed for the two treatments within bacteria type were similar (p≤0.05).
Keywords: Biofilm; ozone; polyethersulfone; bacillus; clean-in-place; dairy